Allosteric interactions at adenosine A1 and A3 receptors: new insights into the role of small molecules and receptor dimerization - Hill, Stephen J.; May, Lauren T.; Kellam, Barrie; Woolard, Jeanette (Wiley, 2014)
Keywords:adenosine;allosterism;receptor;GPCR;dimerization;biased signalling The purine nucleoside adenosine is present in all cells in tightly regulated concentrations. It is released under a variety of physiological and pathophysiological conditions to facilitate protection and regeneration of tissues. Adenosine acts via specific GPCRs to either stimulate cyclic AMP formation, as exemplified by Gs-protein-coupled adenosine receptors (A2A and A2B), or inhibit AC activity, in the case of Gi/o-coupled adenosine receptors (A1 and A3). Recent advances in our understanding of GPCR structure have provided insights into the conformational changes that occur during receptor activation following binding of agonists to orthosteric (i.e. at the same binding site as an endogenous modulator) and allosteric regulators to allosteric sites (i.e. at a site that is topographically distinct from the endogenous modulator). Binding of drugs to allosteric sites may lead to changes in affinity or efficacy, and affords considerable potential for increased selectivity in new drug development. Herein, we provide an overview of the properties of selective allosteric regulators of the adenosine A1 and A3 receptors, focusing on the impact of receptor dimerization, mechanistic approaches to single-cell ligand-binding kinetics and the effects of A1- and A3-receptor allosteric modulators on in vivo pharmacology.